(untitled) (Journal of Educational Sciences, 2023)
Nowadays, a lot of attention is concentrated to the development of education in our country. An important component in the work of a modern teacher is professional success. Each teacher in his work should strive to achieve success in order to get professional motivation from the quality work which is done and provide the necessary level of students’ knowledge. One of the substantial factors that impact the organization of successful work is the organization of work, relations with the teaching staff, parents & students, as well as the ability to show the implementation of their professional qualities. Pedagogical abilities help to assure the accumulation of fertile information that stimulate the formation of self-control and self-regulation, therefore providing the teacher’s need for self-development and self-affirmation. One of the components of the professional success of modern teachers is continuous education and self-improvement in the framework of mastering new means of ensuring professional excellence. In connection with the preceding, the author of this article, having analyzed the views of Sh.A.Amonashvili, A.G.Asmolov, N.M.Borytko, D.V.Grigoriev, A.N. Lutoshkin, A.S. Makarenko, R.S. Nemov, P.V.Stepnov, I.Yu. Shustov presents the main levels of development of the teaching staff. It also analyzes the strategies for cooperation of pedagogy in Europe and the USA.The article attempts to scientific analysis and critical understanding of the problem of development of teachers’ professional success, based on pedagogical cooperation. The practical part of the study includes a survey of 50 teachers on the problem of using strategies of pedagogical cooperation in the team to solve current educational problems, including those related to inclusive education. Key words: Education, pedagogical cooperation,professional success of teachers,teaching staff,ungraded school, interaction.